2016
DOI: 10.1016/j.cgh.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Burden of Nonalcoholic Fatty Liver Disease in a United States Cohort of Veterans

Abstract: Background & Aims Nonalcoholic fatty liver disease (NAFLD) is the leading cause of chronic liver disease in the United States (US). However, few data are available on recent trends in the incidence and prevalence of NAFLD in the US. Methods We analyzed the national Veterans Administration (VA) databases from 2003 to 2011 and calculated the age-adjusted prevalence and incidence of NAFLD for the overall sample of patients and by demographic subgroups. We used a previously validated algorithm to define NAFLD, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 19 publications
2
108
2
Order By: Relevance
“…Another notable result is the rapid projected increase in individuals with cirrhosis, especially decompensated cirrhosis that is cost and resource-intensive [53][54][55]. Increased incidence of decompensated cirrhosis would be expected to have a proportionate impact on healthcare resources and costs associated with advanced liver disease [55,56], and magnify the negative consequences of increasing disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Another notable result is the rapid projected increase in individuals with cirrhosis, especially decompensated cirrhosis that is cost and resource-intensive [53][54][55]. Increased incidence of decompensated cirrhosis would be expected to have a proportionate impact on healthcare resources and costs associated with advanced liver disease [55,56], and magnify the negative consequences of increasing disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there are no true population based incidence data reported for NAFLD. However, Kanwal and colleagues 10 have suggested that the annual incidence of NAFLD based on liver enzyme levels in veterans from the USA who were younger than 45 years old increased from 2.32% to 4.26% (P <0.001). Furthermore, NAFLD is known to be highly associated with several meta bolic conditions (T2DM, obesity, the metabolic syn drome, hypertension and hyperlipid aemia) 22,23 .…”
Section: Key Pointsmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD), defined as excess accumulation of fat in the liver, has become the most common cause for chronic liver disease in the Western world and is estimated to impact at least 30% of Americans1 2 or Chinese3 with the prevalence appearing to rise in recent years 4 5. Non-alcoholic steatohepatitis (NASH) is a subset of NAFLD, estimated to affect 2–5% of Americans, in which increased liver fat is accompanied by cellular injury, inflammatory infiltrate and, subsequently, liver fibrosis, which can progress to cirrhosis with its associated complications 6.…”
Section: Introductionmentioning
confidence: 99%